A Nucleus-Localized Long Non-Coding RNA Enhances Drought and Salt Stress Tolerance. Issue 3 (8th September 2017) - Qin, Tao; Zhao, Huayan; Cui, Peng; Albesher, Nour; Xiong, Liming
Abstract : A long noncoding RNA enhances Arabidopsis tolerance to drought and salt stress by modulating the expression of stress-related genes. Abstract: Long noncoding RNAs (lncRNAs) affect gene expression through a wide range of mechanisms and are considered as important regulators in many essential biological processes. A large number of lncRNA transcripts have been predicted or identified in plants in recent years. However, the biological functions for most of them are still unknown. In this study, we identified an Arabidopsis ( Arabidopsis thaliana ) lncRNA, DROUGHT INDUCED lncRNA ( DRIR ), as a novel positive regulator of the plant response to drought and salt stress. DRIR was expressed at a low level under nonstress conditions but can be significantly activated by drought and salt stress as well as by abscisic acid (ABA) treatment. We identified a T-DNA insertion mutant, drir D, which had higher expression of the DRIR gene than the wild-type plants. The drir D mutant exhibits increased tolerance to drought and salt stress. Overexpressing DRIR in Arabidopsis also increased tolerance to drought and salt stress of the transgenic plants. The drir D mutant and the overexpressing seedlings are more sensitive to ABA than the wild type in stomata closure and seedling growth. Genome-wide transcriptome analysis demonstrated that the expression of a large number of genes was altered in drir D and the overexpressing plants. These include genes involved in ABA signaling, water transport, and other stress-relief processes. Our study reveals a mechanism whereby DRIR regulates the plant response to abiotic stress by modulating the expression of a series of genes involved in the stress response.